Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Project Based Learning (PjBL) pada Pembelajaran Pendidikan Pancasila Kelas III SD Negeri 18 Sungai Nanam Kabupaten Solok - Harmayanti, Yulia; Waldi, Atri; Astimar, Nelly; Ladiva, Hasmai Bungsu (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve the results of students in learning Pancasila Education using the Project Based Learning (PjBL) model in grade III of SD Negeri 18 Sungai Nanam, Solok Regency. This type of research is Classroom Action Research (PTK) This research is carried out in two cycles, with research procedures consisting of planning, implementation, observation, and reflection. The collection technique uses observation and tests. The subjects of this study are teachers and students of grade III SD Negeri 18 Sungai Nanam which totals 31 students. The results of the study showed that the teaching module of the first cycle was obtained on average 87.5% (B), increasing in the second cycle to 95.8% (SB). The results of the implementation of teacher aspect learning in the first cycle were obtained on average 90.6% (B), increased in the second cycle to 96.8% (SB). The results of the implementation of learning aspects of students in the first cycle were obtained on average 87.5% (B), increasing in the second cycle to 96.8% (SB). The learning outcomes of students in the first cycle were obtained on average 71.18% (K), increasing in the second cycle to 82.88% (B). Thus, it can be concluded that the Project Based Learning (PjBL) model can improve the learning outcomes of students in learning Pancasila Education in Class III of SD Negeri 18 Sungai Nanam, Solok Regency